"Double-edged sword": the effect of cultural distance on post-disaster tourism destination recovery. Issue 1 (5th August 2021) - Huang, Li; Zheng, Qingyan; Yin, Xin; Luo, Mingzhi; Yang, Yang
Abstract : Purpose: Some researchers have found that disasters may have a "blessing in disguise effect" that some disaster sites transformed into more popular tourism destinations; however, no studies have analyzed the heterogeneity of the "blessing in disguise effect". This paper aims to explore and determine the effect of cultural distance on international inbound tourist arrivals to a post-disaster tourist destination that could explain this heterogeneous phenomenon. Design/methodology/approach: This study used a threshold regression model and a differences-in-differences (DID) approach to analyze 2000–2016 international tourist arrival data from 13 main origin countries to Sichuan Province before and after the 2008 Wenchuan Earthquake in China. Findings: The effect of cultural distance on post-disaster inbound arrivals from the various origin countries followed a non-linear U-shaped "double-edged sword" pattern rather than displaying a simple linear relationship. Most notably, the disaster appeared to have a more positive effect on arrivals from countries with larger cultural distances, while the effect on arrivals from countries with shorter cultural distances was negative. Originality/value: This study found that cultural distance could explain the heterogeneous "blessing in disguise" phenomenon, and it had both positive and negative impacts on tourism destination recovery; that is, a definite "double-edged sword effect" of cultural distance was found, which could help destination marketing organizations and management departments to design appropriately targeted marketing for post-disaster tourism destination recovery. Abstract : "双刃剑"：文化距离对灾后旅游目的地恢复的影响" 研究目的: 些研究人员发现, 灾难可能会产生"因祸得福效应", 即一些灾难现场变成了更受欢迎的旅游目的地。然而, 目前还没有研究分析这种"因祸得福效应"的异质性。本研究旨在探讨文化距离对灾后旅游目的地的国际入境旅游流的影响, 从而解释这种异质性现象。 研究设计/方法: 本文采用门槛回归模型和双重差分法（DID）分析了2008年汶川地震发生前后（2000–2016年）来自13个主要来源国到中国四川省旅游的国际入境旅游流数据。 结果: 文化距离对灾后客源国的入境旅游人数的影响呈现非线性的U型"双刃剑"模式, 而不是简单的线性关系。最值得注意的是, 灾难似乎对来自文化距离较大的客源国的游客人数产生了更积极的影响, 而对来自文化距离较短的客源国的游客人数产生了消极的影响。 原创性/价值: 本研究发现, 文化距离可以解释异质性的"因祸得福"现象, 文化距离对旅游目的地恢复既有积极影响, 也有消极影响, 即文化距离具有明确的"双刃剑效应"。这可以帮助旅游目的地的灾后恢复设计合理的、有针对性的营销策略和恢复政策。 Abstract : Espada de doble filo": el efecto de la distancia cultural en la recuperación de un destino turístico después del desastre Propósito: Algunos investigadores han encontrado que los desastres pueden tener la "bendición del efecto disfraz" de que algunos sitios de desastre se transformen en destinos turísticos más populares;Sin embargo, ningún estudio ha analizado la heterogeneidel "efecto de bendición disfrazado".El objetivo de este estudio es explorar y determinar el efecto de la distancia cultural en los flujos turísticos internacionales hacia un destino turístico después del desastre, lo que podría explicar este fenómeno heterogéneo. Diseño/metodología/enfoque: se empleun modelo de regresión de umbral y un enfoque de diferencias en diferencias (DID) para analizar los datos de llegada de turistas internacionales de 2000–2016 de trece países de origen principal A la provincia de Sichuan antes y después del terremoto de Wenchuan de 2008 en China. Conclusiones: el efecto de la distancia cultural en las llegde los diversos países de origen después del desastre siguió un patrón de "espada de doble filo" no lineal en forma de u, en lugar de mostrar una relación lineal simple.Más notablemente, el desastre pareció tener un efecto más positivo en las llegde países con distancias culturales más grandes, mientras que el efecto en las llegde países con distancias culturales más cortas fue negativo. Originalidad/valor: este estudio encontró que la distancia cultural podría explicar el heterogéneo fenómeno de la "bendición disfrazada" y que tenía impactos tanto positivos como negativos en la recuperación de un destino turístico;Es decir, se encontró un "efecto de doble filo" de la distancia cultural, que podría ayudar a las organizaciones de comercialización de destinos turísticos y a los departamentos de administración a diseñar estrategias de comercialización dirigidas adecuadamente para la recuperación de destinos turísticos después del desastre.